The impact of some macroeconomic indicators on exchange rate fluctuations in Sudan in the period (1990- 2016) - Tayfor, Abdelsamie Eltaeb (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the determinants and economic variables that affect the exchange rate in Sudan during the period (1990- 2016). The study used the descriptive analytical approach in data collection and analysis as well as the use of econometric methods in the construction of economic models and analysis of time series regression models to verify the existence of a long- term integrative relationship between independent variables and dependent variable. The results of the study showed a positive correlation between GDP, degree of economic openness, inflation and exchange rate during the study years, and an inverse relationship between money supply and exchange rate. The study recommended the need to move away from administrative decisions in determining the exchange rate, while achieving greater flexibility in the exchange rate, and increased interest in bank financing of projects that lead to increase productivity and improve GDP and thus improve the exchange rate by encouraging domestic exports.